Seroprevalence of Filovirus Infection of Rousettus aegyptiacus Bats in Zambia. (8th June 2018) - Changula, Katendi; Kajihara, Masahiro; Mori-Kajihara, Akina; Eto, Yoshiki; Miyamoto, Hiroko; Yoshida, Reiko; Shigeno, Asako; Hang'ombe, Bernard; Qiu, Yongjin; Mwizabi, Daniel; Squarre, David; Ndebe, Joseph; et al.
Abstract: Bats are suspected to play important roles in the ecology of filoviruses, including ebolaviruses and marburgviruses. A cave-dwelling fruit bat, Rousettus aegyptiacus, has been shown to be a reservoir of marburgviruses. Using an enzyme-linked immunosorbent assay with the viral glycoprotein antigen, we detected immunoglobulin G antibodies specific to multiple filoviruses in 158 of 290 serum samples of R aegyptiacus bats captured in Zambia during the years 2014–2017. In particular, 43.8% of the bats were seropositive to marburgvirus, supporting the notion that this bat species continuously maintains marburgviruses as a reservoir. Of note, distinct peaks of seropositive rates were repeatedly observed at the beginning of rainy seasons, suggesting seasonality of the presence of newly infected individuals in this bat population. These data highlight the need for continued monitoring of filovirus infection in this bat species even in countries where filovirus diseases have not been reported.